Rethinking Urbanization in Ancient India: Spatial Patterns, Regional Trajectories and a GIS-Based Historical Approach - Dr. Jamil Ahmed (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This research paper presents a comprehensive framework for analyzing the urbanization of ancient India using Geographic Information System (GIS) technology. It focuses on understanding the spatial distribution and development of ancient city settlements, a subject of great historical interest and significance. The study aims to bridge existing gaps in the literature by offering new insights into the urbanisation process in ancient India and its implications for historical and cultural narratives. Employing a meticulous approach, the paper conducts a thorough literature review, identifying key scholarly works that provide foundational knowledge on the topic. The methodology combines historical records with advanced GIS analysis, creating a novel intersection of historical data and modern technology. This approach facilitates a detailed examination of the spatial dynamics of ancient city settlements across various historical periods. The results reveal significant patterns in urban growth, trade networks, and cultural interactions, further elaborated upon in the discussion section. The analysis interprets these findings in the context of their historical significance, providing a deeper understanding of ancient urban centers and their evolution. The paper concludes by summarizing the main findings and discussing their broader implications, particularly in urban planning, historical research, and cultural studies. The research not only contributes to the academic discourse on ancient Indian urbanization but also offers valuable lessons for contemporary urban development strategies.